Los Goat Production Systems in the Municipality of Molagavita on the Chicamocha River Basin, Colombia - Vargas, Javier Enrique; Serrano, Cesar Augusto; Martínez, Daniel Adyro; Rodríguez , Guadalupe; Zaragoza, Lourdes; Serrano, Lady Katerine (Spei Domus, 2015)
Introduction: The municipality of Molagavita (Colombia) is part of the Chicamocha river basin, where farming and livestock activities are carried out, especially goat breeding. The aim of the research was to identify the characteristics of Molagavita goat production systems present on the Chicamocha river basin. Materials and methods: Snowball sampling was conducted; six producers were surveyed. The survey consisted of 10 parameters with information on general characteristics, population, animal nutrition and feeding, health, reproduction, production, genetics, management, and economics and marketing; the opinion of producers on the production system used and their satisfaction was obtained. Microsoft Office Excel® 2010 was used for analysis, and a descriptive analysis for quantitative variables was implemented. Results: 100% own their land and extension of farms is 7 ± 8.62 ha on average. With regard to infrastructure and equipment used, there are corrals, salting facilities, and troughs in 100% of farms and electric fence in 50%. The production system is extensive in 66%, and oriented towards meat production in 100%. No record is kept and, when finding out about some zootechnical parameters, averages for birth weight of 2.75 ± 0.69 kg and benefit weight 29.5±9.35 kg were reported. Conclusions: The main economic activity in the area is the marketing of goats, poultry, and agricultural products.